Language, migration and continuity of being : notions of migrant language proficiency and self-concept among multilingual migrants in Aotearoa-New Zealand - Walker, Ute Gerda (Massey University, 2004)
Migration entails adjustment and change, a process crystallized in the way language use patterns, proficiencies and identifications change. Although migrants are often bi/ multilingual, their language proficiency tends to be associated with fluency in the host language. Such a monolingual approach is fundamentally at odds with the ethnolinguistic diversity in migration contexts and has prevented a more holistic approach to the dynamic realities of bi/multilinguals. It has also perpetuated a view of linguistic proficiency as technical skill, judged according to idealized monolingual norms. Little is known of speakers' own notions of proficiency in their existing migrant languages (ML) and the impact on their socialpsychological makeup as their linguistic repertoire undergoes changes in use, function and status. This research investigated proficiency as a matter of conceptualization through its users, including its role for migrants' continued sense of self in the face of sociolinguistic discontinuities. A three-phase research design involving focus groups, a postal survey and follow-up interviews was used with a sample of migrants from a wide range of ethnolinguistic backgrounds. The study found evidence for a multidimensional conceptualization of migrant language proficiency (MLP) with a complex range of underlying motivations and a strong emotional attachment to ML, revealing ML as a linguistic resource crucial for self-construction. The present study aimed to provide a deeper understanding of the dynamic nature of these matters to contribute to a socio-culturally grounded view of proficiency and self-concept to help reveal some of the complex processes associated with migrants' social, cultural and psychological wellbeing. The study proposes bi/multilingualism as a settlement target to facilitate this outcome and to foster a sense of self that accommodates multiple identities. Investment in languages promotes an inclusive society of global citizens and complements New Zealand's official Māori/English bilingualism.
Keywords: Immigrants; Language; Bilingualism; Language attrition; Language maintenance; New Zealand; Fields of Research::420000 Language and Culture::420100 Language Studies::420199 Language studies not elsewhere classified